The moderating role of profitability on corporate governance and tax avoidance - Wardani, Dewi Kusuma; Pratiwi, Eka Nur (Proceeding International Conference on Accounting and Finance, 2026)
This study is conducted to examine the effect of good corporate on tax avoidance, with profitability serving as the moderating variable. The proxy for good corporate governance in this study is the audit committee. This study employs a quantitative approach using secondary data processed with SPSS version 25. The financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) are used as the research objects. The dataset consists of 45 manufacturing companies. The results of this study indicate that the audit committee has no effect on tax avoidance, and the profitability variable does not moderate the relationship between corporate governance and tax avoidance.